LIBRARY AND INFORMATION SCIENCE LITERATURE IN BANGLADESH:A BIBLIOMETRIC STUDY - Islam Khan, M.Shamsul; Zabed Ahmed, S.M.; Uddin Munshi, Md. Nasir; Akhter, Nilufar (Malaysian Journal of Library and Information Science, 1998)
Presents the results of a statistical analysis of the papers on various aspects of library and information science (LIS) emanated from Bangladesh during 1966-1997. The analysis is based on a list of papers compiled to show the growth and size of the LIS literature in Bangladesh, patterns of their distribution by subjects within the field of librarianship, characteristics of the contributing periodicals, language of publication, authorship patterns, and geographic distribution of the periodicals. The results of the study showed that, during 1966-1997, a total of 308 articles, authored by 116 library professionals were published in various periodicals with the highest number (256, 83.11%) in Bangladesh, followed by India (21, 6.82%). All these papers were published in some 37 periodicals originating from 14 countries. About 92% of the articles were credited to the single authorship; only 25 articles were co-authored. Problems in library research in Bangladesh have also been discussed, and some suggestions have been put forward to improve the overall situation.